Multi-Sensorial Biofeedback Augmented Horror Games - Gabriel Martins Souto (2017)
Throughout the history of video games, there has been an enormous evolution in their graphic capabilities. However, for a long the interaction with the player was only made with the same types of peripherals, namely with a mouse and keyboard or with a command. It was only decades later that other innovative devices started to appear, beginning with Eye Toy (2003), eventually expanding to other devices such as Kinect (2010), Oculus Rift (2013) and Biofeedback devices. The introduction of this type of devices has altered the potential of video games as it has allowed them to have a greater immersion capability. Biofeedback arose in the 1980s and it can be split in two types, direct or indirect. Direct Biofeedback, which requires conscious user participation (for example, by moving your body), knowing how your data affects the program, or indirect, that involves collecting data from the player without it (measuring heart rate or the skin's conductivity), the latter being of great interest because it is possible, from these sensors, to infer the player's emotions and to adapt the game itself to the player's emotional states, allowing a more personalised and realistic experience.To make the experience as captivating as possible, different peripherals will be used in situations where they make more sense, that is, when an in-game action should be more difficult or a special skill.These peripherals will be integrated in a horror game, having as a study case an experimental comparison between the different combinations of game mechanics to see which will provide greater immersion, how exhaustive these combinations would be and the advantages and disadvantages of such combinations.